AN ANALYSIS OF STUDENTS’ ERRORS USING SIMPLE PAST TENSE IN WRITING NARRATIVE TEXT AT GRADE X OF MAS TELADAN UJUNG KUBU IN 2023/2024 ACADEMIC YEAR - Sidabalok, hamidah; Hasibuan, Derliana; Sambayu, Harry (Universitas Asahan, 2024)
The goal of this study was to assess students' procedural text writing skills. This study was conducted at MAS Teladan Ujung Kubu. One month was allotted for this study's duration. This study used a descriptive, quantitative research design. Random sampling was the technique used to collect the sample. The four classes of grade X pupils that made up the research population were all of them. There were 159 pupils in all, 40 students in each of the three classes and 39 students in the single class. The researcher selected X-4, including 39 pupils, as the research sample because this study used descriptive quantitative methods. A test was one of the research's instruments. It was an essay-based test. Keywords : Kabupaten Asahan, Errors Analysis, Writing, Narrative Text.